A MINLP model for the layout design of subsea oil gathering - transportation system in deep water oil field considering avoidance of subsea obstacles and pipe intersections. (1st June 2023) - Hong, Cheng; Wang, Yuxi; Estefen, Segen F.
Abstract: This paper focuses on the layout design of subsea oil gathering-transportation system in deep water oil field. In such a system, subsea manifolds are applied to gather and transport the produced fluids from subsea wells to floating processing terminals. A mixed integer nonlinear programming (MINLP) model is proposed, constrained by a series of operation and production requirements, aiming to minimize the total layout cost. Through the model, the pipe line network topology structure which reflects the allocations among the subsea wells, manifolds and processing terminals, the routes of pipes, as well as the size of the facilities could all be figured out. Two key contributions are made through this work. First, avoiding pipe intersections and subsea obstacles are integrated simultaneously, making the proposed model closer to practical situations. Second, a decomposition strategy based on Delaunay triangulation and gradient descent is constructed, achieving high quality initial solution and stable iteration process. The results of case studies indicate the validity, feasibility and stability of the proposed model and the solution method. Besides, the effect of manifold numbers on the layout optimization result is analyzed through the model, indicating its flexibility in the layout design analysis. Highlights: A MINLP model is built to optimize subsea oil gathering-transportation system layout. Avoiding pipe intersections and subsea obstacles are integrated simultaneously. Solution strategy combined Delaunay triangulation and gradient descent is developed. Case studies indicate the model's feasibility, stability and flexibility. The results considering different manifold numbers are compared and analyzed.